2017
DOI: 10.1186/s40479-017-0072-6
|View full text |Cite
|
Sign up to set email alerts
|

A pilot open series of lamotrigine in DBT-treated eating disorders characterized by significant affective dysregulation and poor impulse control

Abstract: BackgroundThere is little effective psychopharmacological treatment for individuals with eating disorders who struggle with pervasive, severe affective and behavioral dysregulation.MethodsThis pilot open series evaluated lamotrigine, a mood stabilizer, in the treatment of patients with eating disorders who did not respond adequately to antidepressant medications. Nine women with anorexia nervosa- or bulimia nervosa-spectrum eating disorders in partial hospital or intensive outpatient dialectical behavior thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 73 publications
2
7
0
Order By: Relevance
“…These analyses are limited by the nature of the data collection procedures (e.g., variability in the time frame before and after prescription); however, they do provide some preliminary evidence that that in a group of patients who reports significant affective lability and impulsivity, prescription of lamotrigine is associated with a significant decrease in self-reported emotional reactivity and impulsivity. Of note, these patients did not report significant changes in skills use, emotional reactivity, and impulsivity prior to taking lamotrigine despite being enrolled in the DBT program, consistent with the clinical prediction that lamotrigine may enable patients to better engage with and benefit from the treatment [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These analyses are limited by the nature of the data collection procedures (e.g., variability in the time frame before and after prescription); however, they do provide some preliminary evidence that that in a group of patients who reports significant affective lability and impulsivity, prescription of lamotrigine is associated with a significant decrease in self-reported emotional reactivity and impulsivity. Of note, these patients did not report significant changes in skills use, emotional reactivity, and impulsivity prior to taking lamotrigine despite being enrolled in the DBT program, consistent with the clinical prediction that lamotrigine may enable patients to better engage with and benefit from the treatment [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 60%
“…With regard to its effectiveness for treating EDs, an initial case series of five patients within our program indicated that concurrent lamotrigine, often alongside an antidepressant medication, and DBT were associated with decreases in mood reactivity, impulsive behaviors, and ED behavior [ 19 ]. Results from a second open trial revealed significant decreases in impulsive and dysregulated behaviors when lamotrigine was added to DBT and concurrent selective-serotonin reuptake inhibitors (SSRIs) for nine women with EDs [ 20 ]. However, given that these investigations evaluated the simultaneous use of DBT and lamotrigine, it is unclear whether lamotrigine provides additive benefit over and above DBT.…”
Section: Introductionmentioning
confidence: 99%
“…These interventions are consistent with the goals of Interpersonal and Social Rhythm Therapy, a form of therapy developed for individuals with bipolar disorder . Emotional regulation and distress tolerance are also important for Dora and are core skills in Dialectical Behavior Therapy (DBT); another form of therapy with evidence of effectiveness in stabilizing moods and avoiding relapse of eating disorder and mood disorder symptoms …”
Section: A Clinical Casementioning
confidence: 75%
“…IDS families brought their children in at ages 3 ( Wave 1), 6 (Wave 2), 12 (Wave 3), and 24 months (Wave 4) for questionnaires, diagnostic interviews, and laboratory 1 The authors recognize the potential controversy in including eating pathology as part of internalizing disorder, given its manifestation that is not as clear with mood and anxiety disorders. However, many conceptualizations of eating disorders posit that poor affective regulation is a core feature (e.g., Hayaki, 2009;Trunko et al, 2017). In order to address this concern all analyses presented in the paper were re-run excluding eating disorders.…”
Section: Participantsmentioning
confidence: 99%